Comparison of dental anxiety among patients visiting a dental college and private dental clinics in Thiruvallur district, India - R Ganesh; Chandasmita Goswami; Rumana Munshi (Wolters Kluwer Medknow Publications, 2014)
Background: The objective of the study was to assess and compare the prevalence of dental anxiety based on age and gender distribution among the patients reporting at private dental clinics in Thiruvallur district and in private dental college, Thiruvallur. Materials and Methods: The sample comprised of 230 patients, out of which 115 patients randomly selected from the private dental clinics and other 115 patients from Priyadarshini Dental College and Hospital, Thiruvallur. Modified Dental Anxiety Scale (MDAS) was used to assess the anxiety level of the patients. Result: A total of 115 patients in dental college and 115 patients in dental clinics were questioned in the study. Out of these, 13% of patients in dental college and 20.90% of patients in dental clinics were severely anxious. A total of 4.30% of patients in dental college and 3.50% of patients in dental clinics were not anxious at all. The ratio of rate of anxiety of female patients was greater than males. Conclusion: The prevalence of dental anxiety among the patients in this study was high. This highlights the need for dentists to understand what patients feel about dental treatment procedures and aid dentist efforts to improve patients care.